Islam in Maintaining Health of Water and Air - Noor Latifah; Fini Fajrini; Dadang Herdiansyah; Nadilla Firda; Abul A’la Al Maududi (Indonesian Journal of Islam and Public Health, 2022)
Many verses of the Quran and Hadith that explains, recommends and even obliges every human being to maintain the continuity of life and the life of other creatures on earth. So, as the representative of Allah on earth, humans must be active and active responsible for protecting the earth. It means, maintaining continuity the function of the earth as a place of life for God's creatures including humans while maintaining the sustainability of life. In this context, nature, especially the earth, is where humans live is a testing ground for humans. Islam protects the environment in order to protect water and air from pollution because water and air are very useful and play a role in the life of living things on this earth, it is important for us to always preserve and maintain the sustainability of the water we use by doing good water management such as saving, not throwing garbage and waste that can make water pollution so that it can disrupt the existing ecosystem. A good environment will produce good oxygen in protecting the earth from various things including from various celestial bodies that fall to earth.